Association of multimodal analgesia with perioperative safety and opioid use following head and neck microvascular reconstruction. Issue 10 (20th July 2020) - Sayal, Navdeep R.; Militsakh, Oleg; Aurit, Sarah; Hufnagle, John; Hubble, Lester; Lydiatt, William; Lydiatt, Daniel; Lindau, Robert; Coughlin, Andrew; Osmolak, Angela; Panwar, Aru
Abstract: Background: This study examines the association of multimodal analgesia (MMA) protocol for head and neck microvascular reconstruction with postoperative safety and opioid use. Methods: Retrospective, intention‐to‐treat analysis of 226 patients undergoing head and neck microvascular reconstruction between January 1, 2014 and August 30, 2018 at a tertiary‐care hospital following MMA protocol implementation. Multivariable models examined outcomes of interest. Results: There were no differences between groups in frequency of bleeding, return to operating room, complete flap loss, readmissions, wound complications, and 30‐day mortality. Patients in MMA protocol experienced reduced likelihood of partial flap loss (OR 0.18, confidence interval 0.04‐0.91), meaningful reduction in postoperative opioid use (cumulative inpatient morphine equivalents [64 vs 141 mg; P  < .001], daily morphine equivalents [8 vs 22 mg/d; P  < .001]; and 22.5% lower frequency of opioid prescription at discharge [55.6% vs 78.1%; P = .001]). Conclusions: In patients undergoing head and neck microvascular reconstruction, MMA is safe and associated with reduced postoperative opioid use.